The Role of Marriage Development and Preservation Advisory Agency In Anticipating Divorce Rate - Abdul Hakim; Ali Bata Ritonga (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
The big point of this research is how does the role of advising council and preservation of marriage as the council of advising and preservation of marriage at the regency of Labuhanbatu Raya contribute. The purpose of this research is to analyze about the role of advising council and preservation of marriage as the council of advising and preservation of marriage at regency of Labuhanbatu Raya which was provided by the government. socialization about honesty marriage, mawaddah, wa rahma and piety. And the affordability of BP4 to oppress the divorce rates at the regency of Labuhanbatu Raya is going spirit to do national movement, this program is running well as the founding honest marriage for every month based on frame work and reformation agenda on social custom and affordable to create the highest communities' moral, faithful, worship and honorable attitude. Meanwhile the obstruction factor divided into internal and external. And the support factor is the communities hope and support toward being on having an honest marriage